Teaching electrolysis of water through drama - (:unkn) unknown (My University, 2010)
The purpose of this study was to evaluate the effects of drama on the teaching of electrolysis of water to middle school students. The randomized pre-test and post-test control group design was used. Data collection methods included pre-test, post-test 1 and 2, and the data were analyzed by using the SPSS/PC program. This study was carried out at a private school with 40 seventh grade students. Based on the pre-test results, the students were randomly assigned to drama and control groups. Findings suggest that the drama group performed better than the control group both on post-test 1 and post-test 2. Similar studies in different contexts with different student samples may be conducted to investigate the effects of drama in chemistry education.
Keywords: Chemistry education; Drama in science education; Electrolysis of water